Sebuah Pengaruh Motivasi, Supervisi, dan Etika Auditor Terhadap Kualitas Audit: (Studi kasus pada Kantor Akuntan Publik di Bandung Tahun 2019) - Sormin, Piter Chris Daniel; Rahayu, Sri (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
This research was conducted to find out and obtain empirical evidence simultaneously and partially regarding the Effect of Auditor Motivation, Supervision, and Ethics on Audit Quality (Case study at the Public Accountant Office in Bandung). The population in this study were all auditors of Public Accountant Firms located in the City of Bandung. This study uses 32 auditors as respondents. The data analysis method used in this research is multiple linear regression analysis methods. Simultaneously the auditor's motivation, supervision, and ethics variables influence audit quality. Motivation partially has no significant effect on audit quality. Supervision and Auditor’s Ethics partially have a significant effect on audit quality. In subsequent studies, other researchers can use the research object and also add other independent variables to measure audit quality. Public accounting firms are expected to motivate auditors through conducting seminars on the sciences or steps to improve auditor's ethical standards and professional skills